2012
DOI: 10.1007/s00406-012-0353-4
|View full text |Cite|
|
Sign up to set email alerts
|

Stress, burnout, and job dissatisfaction in mental health workers

Abstract: As the industrial world has transformed toward a service economy, a particular interest has developed in mental health problems at the workplace. The risk for burnout is significantly increased in certain occupations, notably for health care workers. Beyond the effects of an extensive workload, many working hours, or long night shifts, the medical field has specific stressors. Physicians work in emotionally demanding environments with patients, families, or other medical staff. They must make quick decisions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
137
1
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 23 publications
5
137
1
10
Order By: Relevance
“…As the risk for job distress and staff burnout has significantly increased for mental health workers (Rossler, 2012); mental healthcare delivery and improving staff psychological well-being have required increased attention (Lasalvia et al, 2009). Avey, Luthans, Smith, and Palmer (2010) suggest that personal psychological well-being leads to desired outcomes in both personal life, and in work settings.…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…As the risk for job distress and staff burnout has significantly increased for mental health workers (Rossler, 2012); mental healthcare delivery and improving staff psychological well-being have required increased attention (Lasalvia et al, 2009). Avey, Luthans, Smith, and Palmer (2010) suggest that personal psychological well-being leads to desired outcomes in both personal life, and in work settings.…”
Section: Psychological Well-beingmentioning
confidence: 99%
“…Psychiatry itself adds several very specific stressors such as perceived stigma of this profession, demanding therapeutic relationships, personal threats from violent patients and patient suicide (12).…”
Section: Introductionmentioning
confidence: 99%
“…Compared against other professions, studies have shown that the mental health workforce faces many unique challenges and stressors, including the stigma surrounding mental health, secondary exposure to client trauma, client suicides, and high productivity demands coupled with low pay (Chemtob, Hamada, Bauer, Kinney, 1998;Rossler, 2012). Moreover, relative to other private sector industries, the mental health sector has a higher incidence of workplace violence (Privitera, Weisman, Cerulli, Tu, & Groman, 2005).…”
mentioning
confidence: 99%